RNAi silencing of brain klotho potentiates cold-induced elevation of blood pressure via the endothelin pathway - Wang, Xiuqing (American Physiological Society, 2010)
Klotho is a recently identified antiaging gene. Brain endothelin-1 (ET1) is important in the regulation of blood pressure (BP). We hypothesized that silence of brain klotho potentiates cold-induced elevation of BP via the endothelin pathway. To silence brain klotho, we constructed adeno-associated virus (AAV) carrying rat klotho small interference hairpin RNA (KL-shRNA). AAV carrying ET1-shRNA was used to silence brain ET1. Scrambled shRNA was used as Control-shRNA. Three groups of male Sprague-Dawley rats (6 rats/group) received KL-shRNA, KL-shRNA plus ET1-shRNA, and Control-shRNA, respectively, via intracerebroventricular injection. BP was monitored daily using a telemetry system. All animals were exposed to a moderate cold environment (5°C) at 12 days after gene delivery. KL-shRNA significantly increased BP by 9 days of exposure to cold, while BP in the Control-shRNA group remained unchanged. ET1-shRNA abolished KL-shRNA-induced elevation of BP during cold exposure. Interestingly, KL-shRNA increased brain ET1 expression and plasma norepinephrine level, suggesting that silencing of brain klotho increased ET1 production and the sympathetic nervous activity. The KL-shRNA-induced increase in sympathetic nervous activity was mediated by ET1 because it could be abolished by silencing of ET1. These results demonstrated that silencing of brain klotho potentiated and expedited cold-induced elevation of BP by upregulation of ET1 and the subsequent activation of the sympathetic nervous system.